The Diana project: a legacy for research on gender in entrepreneurship - Candida G. Brush; Patricia G. Greene; Friederike Welter (Institut für Mittelstandsforschung (IfM) Bonn, 2020)
Purpose: The purpose of this article is to provide a brief history of the evolution of the Diana Project and the Diana International Research Conference. We examine the impact of the publications, conferences and research contributions; and consider key factors in the success of this collaborative research organization. We discuss the ongoing legacy, suggesting ways to extend this into the future. Design/Methodology/Approach: Historical narrative and citation analysis Findings: The Diana Project was founded by five women professors in 1999 to with the purpose of investigating women's access to growth capital. Following a series of academic articles, and numerous presentations, the first Diana International Conference was held in Stockholm, Sweden. At this convening, 20 scholars from 13 countries shared their knowledge of women's entrepreneurship, venture creation and growth, culminating in the first volume of the Diana Book Series. Since then, 14 international conferences have been held, resulting in 10 special issues of top academic journals, and 11 books. More than 600 scholars have attended or participate in Diana conferences or publications. [...] – – Der Beitrag gibt einen Überblick über die Entwicklung des Diana-Projekts und die internationale Forschungskonferenz Diana. Die Autorinnen zeigen dabei sowohl die Wirkung der Veröffentlichungen als auch der Konferenzen und Forschungsbeiträge auf. Zugleich identifizieren sie die Schlüsselfaktoren, die für den Erfolg dieser kooperativen Forschungsorganisation verantwortlich sind.
Keywords: 330; gender; women's entrepreneurship; Diana Project; venture capital; collaborative research